1991
DOI: 10.1111/j.1471-4159.1991.tb03777.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression of Biologically Active Human Glia Maturation Factor‐β

Abstract: Glia maturation factor-beta, a protein found in the brains of all vertebrates thus far examined, appears to play a role in the differentiation, maintenance, and regeneration of the nervous system. Using oligonucleotide probes based on the sequences of three tryptic peptides derived from bovine glia maturation factor-beta, we screened a human brainstem cDNA library in lambda gt11. A 0.7-kb clone was isolated, sequenced in its entirety, and found to encode a polypeptide of 142 amino acids which contained regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 43 publications
1
58
0
Order By: Relevance
“…Glia maturation factor (GMF), a 17 kDa highly conserved protein, with 99% homology between humans and rodents, was isolated, sequenced and cloned in our laboratory (Kaplan et al, 1991;Lim et al, 1989;Zaheer et al, 1993). The GMF gene is localized to the long arm of human chromosome 14 (Lander et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glia maturation factor (GMF), a 17 kDa highly conserved protein, with 99% homology between humans and rodents, was isolated, sequenced and cloned in our laboratory (Kaplan et al, 1991;Lim et al, 1989;Zaheer et al, 1993). The GMF gene is localized to the long arm of human chromosome 14 (Lander et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The Glia Maturation Factor (GMF), a highly conserved brain-specific protein, was isolated, sequenced and cloned in our laboratory (Kaplan et al, 1991;Lim et al, 1989;Lim et al, 1990;Zaheer et al, 1993;Zaheer et al, 1995a;Zaheer et al, 1995b). The functional property of GMF was largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on glia maturation factor (GMF), a brain-specific protein, isolated, sequenced and cloned in our laboratory (Kaplan et al, 1991;Lim et al, 1989;Lim et al, 1990), have given new insights into its role in immunomodulatory and proinflammatory functions in CNS (Lim and Zaheer, 1996;Lim et al, 2000;Zaheer et al, 2002;Zaheer et al, 2004;Zaheer et al, 2006;Zaheer et al, 2007). We have established that overexpression of GMF in astrocytes leads to immune activation of microglia, through secretion of granulocyte-macrophage-colony stimulating factor (GM-CSF), and resulting in production of several pro inflammatory mediators that destroy oligodendrocytes, the myelin forming cells in CNS.…”
Section: Introductionmentioning
confidence: 99%
“…This event apparently thought to be the result of a combined autoimmune response to some of the myelin components (Glynn and Linington 1989;Bernard et al 1997;Steinman and Zamvil 2005;Gold et al 2006). Research efforts in recent years on glia maturation factor (GMF), a highly conserved brain-specific protein, isolated, sequenced and cloned in our laboratory (Lim et al 1989;Lim et al 1990;Kaplan et al 1991;Zaheer et al 1993), have demonstrated an immunomodulatory function for GMF. Recently, it has been established that overexpression of GMF in astrocytes leads to immune activation of microglia through secretion of granulocyte-macrophage-colony stimulating factor (GM-CSF) (Zaheer et al J. Neurochem.…”
Section: Introductionmentioning
confidence: 99%